2013
DOI: 10.4103/0300-1652.108887
|View full text |Cite
|
Sign up to set email alerts
|

The human health implications of crude oil spills in the Niger delta, Nigeria: An interpretation of published studies

Abstract: Background:The health hazards created by oil exploration and exploitation are covert and slow in action. They are not given the deserved attention in official documents in Nigeria, even as they can be major contributors to the disease burden in oil-bearing communities. This study is an interpretation of the data reported in several published studies on crude oil spills in the Niger delta region, Nigeria.Materials and Methods:A manual and Internet search was conducted to extract quantitative data on the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
150
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 15 publications
1
150
0
1
Order By: Relevance
“…Nigeria has recorded high occurrence of oil spillage in the Niger Delta ( Ordinioha and Brisibe 2013) and along pipelines traversing other parts of the country mainly due to sabotage, corrosion and rupture of pipelines, operations and transportation among others (Adelana et al, 2011). According to NOSDRA (2016), oil spillage in Nigeria has escalated to a thousand spills per year, the highest rate of spills worldwide suggesting the need for continuous search of the best methods of cleaning up crude oil to control its negative impacts on the environment.…”
mentioning
confidence: 99%
“…Nigeria has recorded high occurrence of oil spillage in the Niger Delta ( Ordinioha and Brisibe 2013) and along pipelines traversing other parts of the country mainly due to sabotage, corrosion and rupture of pipelines, operations and transportation among others (Adelana et al, 2011). According to NOSDRA (2016), oil spillage in Nigeria has escalated to a thousand spills per year, the highest rate of spills worldwide suggesting the need for continuous search of the best methods of cleaning up crude oil to control its negative impacts on the environment.…”
mentioning
confidence: 99%
“…In 2011, a United Nations Environmental Programme (UNEP) report revealed that drinking water in Ogoniland was found to contain a known carcinogen at levels 900 times above World Health Organization guidelines (United Nations Environment Programme, 2011). In another study, it was found that oil spills reduce the ascorbic acid content of vegetables by as much as 36% and the crude protein content of cassava by 40%, which results in a 24% increase in the prevalence of childhood malnutrition in the region (Ordinioha and Brisibe, 2013). In the same study, it was found that animals that come in contact with crude oil could be hemotoxic (destroying red blood cells) and hepatotoxic (destroying the liver), and could suffer infertility and cancer.…”
Section: Health Implications Of Oil Spills In the Niger Deltamentioning
confidence: 99%
“…This is forcing farmers to travel very long distances from their localities. In terms of health impacts on the locals, [24] argue that the prevalence of diarrhea in the Niger Delta is on the rise, as a result of the consumption of fish and other animals contaminated by hydrocarbons contained in the spilled oil. Furthermore, it has been determined that bioaccumulation of benzo (o) pyrene, other hydrocarbons, and heavy…”
Section: Food Quality/supplymentioning
confidence: 99%